“STUDENT FRIENDLY”POS PELAYANAN REMAJA SEHAT - Fitria Hayu Palupi; Ilma Widyasari (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2016)
ABSTRACTThe teen lifestyle rightnow is so worrying. Most of teenagers have experienced sexual activities since Junior High School. They consider that hugging, holding hands, and kissing are common things to do when they are dating. It, consequently, triggers students to have deviant behaviors, such as drinking alcohol, addicting to drugs or NAPZA, and having free sex. The students actually have been guided through school guidance and counseling to join positive activities. However, it has not been well-realized. By the establishment of “Student Friendly” healthy adolescent service post, it is expected that students are able to do mentoring to their peers in solving reproduction health problems. The outcomes of service community activities are improving students’ knowledge about reproduction health and improving healthy planning generation to the junior and high school students that are mentored by the competent students of STIKes Mitra Husada of Karanganyar who have experienced reproduction health training. By the availability of healthy adolescent service post, the junior and senior high school students can improve and make similar teen groups so that the teens of schools and society are able to actively participate in the adolescent reproduction health and healthy lifestyle. The entire students joining in this activity can be the member of PIK of STIKes Mitra Husada of Karanganyar by which its students as the counselors. ABSTRAKGaya hidup remaja saat ini sungguh sangat memprihatinkan. Sebagian remaja sejak SMP telah melakukan aktifitas seksual. Mereka menganggap bahwa berpelukan, bergandengan tangan serta berciuman merupakan hal yang wajar dilakukan saat berpacaran. Akibat negatifnya perilaku siswa cenderung menyimpang seperti minum minuman keras, menjadi pecandu narkoba atau NAPZA, serta pergaulan bebas (free sex). Melalui bimbingan konseling dia telah dibimbing untuk mengikuti kegiatan kesiswaan namun belum terlaksana dengan baik. Dengan dibentuknya Student friendly pos remaja sehat maka diharapkan para siswa mampu melakukan pendampingan kepada siswa sebaya dalam mengatasi permasalahan kesehatan reproduksi. Luaran dari kegiatan pengabdian masyarakat ini adalah bagi siswa SMP dan pengetahuan siswa mengenai kesehatan reproduksi dan meningkatkan generasi berencana yang sehat yang didampingi oleh mahasiswa STIKes Mitra Husada Karanganyar yang telah berkompeten serta telah mengikuti pelatihan kesehatan reproduksi. Dengan adanya pos pelayanan remaja sehat,maka remaja/siswa SMP dan SMA dapat mengembangkan atau membentuk kelompok remaja serupa sehingga remaja di sekolah maupun di masyarakat ikut berperan serta dalam kesehatan reproduksi remaja dan berperilaku hidup sehat. Semua siswa yang mengikuti kegiatan ini menjadi anggota PIK STIKes Mitra Husada Karanganyar dengan mahasiswa sebagai konselor.